Cybercrime in Ghana A Study of Offenders, Victims and the Law - Ennin, D (University of Ghana, 2015)
The Information and Communication Technology (ICT) has become essential to the operations of government, corporate institutions and individuals, but the benefits accruing from the growing access is being undermined by miscreants who are exploiting its capabilities to the detriment of others. This has tainted Ghana‟s reputation in the global environment. The main thrust of this study was therefore to explore the dynamics of cybercrime activities from the perspectives of offenders, victims and the law. The objectives that guide the research are; 1) to understand the socioeconomic characteristics of offenders and the victims, 2) identify the motivation that predispose the offenders to cybercrime, 3) establish the various forms of cybercriminal activities in Ghana, 4) to find out the opportunities explored by the fraudsters in their operations, 5) explore the experiences of the cybercrime victims, and 6) to examine the responses and challenges of law enforcement agencies to fight cybercrime. The research was situated within the Accra metropolis. The study was largely qualitative but the research design enabled the researcher to combine both quantitative and qualitative strategies to collate data from the field. Snowball and purposive sampling methods were used to reach out 26 respondents. They included 11 internet scammers, 6 victims, 8 key informants from the Criminal Investigation Department of the Ghana Police Service and a Circuit Court judge. All the participants took part in the qualitative study. With regards to the questionnaire, 17 out of the 26 respondents participated and they were made up of victims and the offenders. The findings of the study revealed that cybercrime perpetrators were mostly young men between 17 to 30 years with an average age of 23. The majority of the scammers were from economically deprived homes. With regards to the victims, they are adults who are highly educated and well-to-do in the society. A number of the victims heeded to the scammers request without due diligence. The results of the study further show that a poor legal regime encouraged the youth to indulge in cybercrime. Besides, the Act 772 that supposed to regulate the criminal behaviors in the electronic space is also inadequate to fight the menace in terms of criminalization, evidence and trial of offences. Moreover, the Ghana Police Service lacks the technical know-how and the state-of–the-art equipment to monitor internet fraud. The characteristics of cybercriminals, victims and law enforcement agencies have a reinforcing effect on one another, leading to a vicious cycle of cybercrime. Inability of the police to solve cybercrimes has eroded victims‟ confidence in the criminal justice system, and this has increased criminals‟ confidence to continue their operations. This outcome was consistent with the Routine Activity theory which presupposes that crime can occur when there is no adequate police patrols, effective laws which motivated the offender to commit the crime. The major recommendations that have been outlined to fight the menace are: 1) formulation of appropriate laws to curb cybercrime; 2) government should organize capacity building for law enforcers to enable them abreast with internet fraud issues; 3) government should further establish appropriate facilities to fight the menace; 4) public education should be intensified about the modus operandi of internet scammers; 5) youth focused programmes should be initiated to address youth-unemployment. Finally, further study areas were suggested.
Keywords: CYBERCRIME; GHANA; OFFENDERS; VICTIMS; LAW